“Let me hear what you’re needing”: exploring how HIV providers conceptualize patient-provider interactions with people with HIV who use drugs using a harm reduction framework - Stephanie L. Creasy; James E. Egan; Sarah Krier; Jessica Townsend; Jessica Ward; Mary Hawk; Emma Sophia Kay (Therapeutic Advances in Infectious Disease)
Background: In addition to structural interventions such as syringe services and naloxone distribution, harm reduction (HR) is also a relational approach to care encompassing principles such as patient autonomy and pragmatism that can be implemented in healthcare teams to improve outcomes for people with HIV (PWH) who use drugs. Evidence suggests that using a relational HR framework to operationalize care for PWH who use drugs may improve the patient-provider relationship, thus positively impacting HIV outcomes. We previously found that negative attitudes toward people who use drugs are negatively associated with acceptance of HR; however, little is known about how HIV providers conceptualize the patient-provider relationship with PWH who use drugs. Objectives: The aim of this study was to describe the ways healthcare workers (HCWs) characterize interactions with PWH who use drugs and if these characterizations reflect relational HR or missed opportunities to improve the patient-provider relationship. Design: We used a qualitative descriptive design to characterize HCWs’ descriptions of their interactions with PWH who use drugs. Methods: We interviewed providers ( n  = 23) working at three HIV clinics in the United States to assess their interactions with patients. Providers included anyone who had worked at their respective clinic for ⩾1 year and who had face-to-face contact with patients (e.g., front desk staff, nurses, physicians, and social workers). Data were coded thematically via Dedoose. Results: We discovered that HCWs characterize positive patient-provider interactions that both reflect HR principles and may not align with the principles of HR. Examples include when patients appear comfortable with and trusting of their provider, when patients feel heard by their provider, and when providers feel they are responsive to patient needs. However, other HCWs described positive interactions as counter to relational HR. Conclusion: HCW descriptions of positive interactions in line with relational HR in their conceptualization of patient-provider interactions with PWH who use drugs have the potential to guide efforts in increasing the acceptability of HR in HIV care. Given evidence showing HR improves outcomes for those who use substances, findings suggest missed opportunities to incorporate relational HR into the patient-provider relationship in HIV primary care settings. Registration: NCT05404750.